Compliance of post‐radiation therapy head and neck cancer patients with caries preventive protocols. (June 2017) - Frydrych, AM; Slack‐Smith, LM; Parsons, R
Abstract: Background: Caries prevention is paramount in safeguarding the life quality of head and neck cancer patients and is dependent on patient compliance with caries preventive protocols. The purpose of this study was to examine this compliance. Methods: All records of patients referred to one public oral medicine clinic servicing a head and neck oncology unit of one major Western Australian hospital, between January 2005 and December 2011, were examined. Data extracted included patient and cancer characteristics and compliance with dietary advice, dental care, oral hygiene instruction and fluoride use over a follow‐up period of at least 12 months. Compliance was assessed against various oral health outcomes and patient characteristics. Results: Of the 116 participants, 75.9% complied with all caries preventive measures over a mean follow‐up period of 45 months. Non‐compliance with regular dental attendance ( P = 0.004), oral hygiene instruction ( P = 0.009), dietary advice ( P = 0.034) and daily fluoride use ( P = 0.018) were associated with the development of dental caries post‐treatment. The presence of dental caries at the time of cancer diagnosis was predictive of poorer compliance. Conclusions: High compliance with caries preventive measures is attainable in the head and neck cancer patient group. Factors other than fluoride use seem important in caries prevention.